Implementation of Village Budget Management Policies In An Effort to Improve The Welfare of Village Communities in Klaten District - Minarni, Sarida; Raharjo, Paiman; Soemarono, Triyuni; Effendy, Khasan; Rachmatsyah, T.Herry (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Research of Village Fund for 2024. Government Agency which has Klaten Regency Empowerment Service a an were meanwhile, data analysis techniques are data reduction, data display, conclusion drawing.Research show Management Klaten has carried out the Klaten Regency Regulation 2022 concerning the Klaten Regent Regulation 92 of 2019 Guidelines for Implementing Village Fund Allocation Management. However, in practice, relatively not all work is carried out in an administrative order. Meanwhile, implementation factors are financial. They meanwhile management disposition, it needs to be considered.